DECISION SUPPORT SYSTEM FOR DETERMINING INDIGENT PUBLIC HEALTH INSURANCE PARTICIPANTS WITH WEIGHTED PRODUCT METHOD IN PRINGSEWU - Marlia Sari; Didi Susianto (IJISCS (International Journal of Information System and Computer Science), 2023)
JAMKESMAS to realize health equity is one of the programs implemented by the Government of Indonesia through the Social Service and Health Office, this program is implemented in rural and suburban areas. The JAMKESMAS program is aimed at people who are deprived or have low income in rural areas. With JAMKESMAS, it is hoped that they can get assistance in the health sector in Indonesia. The implementation of this program is in order to support the achievement of targets through mainstreaming and expanding community-based development approaches. However, to determine the participants of JAMKESMAS is very difficult because many people will be selected. This is what makes the author want to do research and create a decision support system so that it is fast in the selection process. The method used is the WP method. The result of this decision support system is that the provision of assistance to JAMKESMAS is right on target for families who really need this assistance.